2016
DOI: 10.1002/14651858.cd011440.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide levels to guide treatment for adults with asthma

Abstract: With new studies included since the last version of this review, which included adults and children, this updated meta-analysis in adults with asthma showed that tailoring asthma medications based on FeNO levels (compared with primarily on clinical symptoms) decreased the frequency of asthma exacerbations but did not impact on day-to-day clinical symptoms, end-of-study FeNO levels, or inhaled corticosteroid dose. Thus, the universal use of FeNO to help guide therapy in adults with asthma cannot be advocated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 48 publications
3
66
0
2
Order By: Relevance
“…Our data therefore extend previously published cross-sectional data in adults 13 and longitudinal data in children, 47 demonstrating various accuracies in discriminating con- biomarker, a recent meta-analysis showed that tailoring asthma therapy based on FE NO reduces asthma exacerbations in adults, even though it does not impact day-to-day symptoms. 49 Our present data are indicating that composite molecular signatures as obtained by GC/MS, and the more so by eNose, are also capturing clinically relevant changes in asthma control.…”
Section: Discussionsupporting
confidence: 60%
“…Our data therefore extend previously published cross-sectional data in adults 13 and longitudinal data in children, 47 demonstrating various accuracies in discriminating con- biomarker, a recent meta-analysis showed that tailoring asthma therapy based on FE NO reduces asthma exacerbations in adults, even though it does not impact day-to-day symptoms. 49 Our present data are indicating that composite molecular signatures as obtained by GC/MS, and the more so by eNose, are also capturing clinically relevant changes in asthma control.…”
Section: Discussionsupporting
confidence: 60%
“…41 However, it is known that eosinophilic inflammation in the airways is most pronounced in atopic asthma, and the concentration of nitric oxide is related to eosinophilic inflammation in the airways. 41,42 FeNO values were significantly higher in the RV group than in controls and in the RSV group, which may be a sign of higher prevalence of eosinophilic inflammation in the airways in initially RVpositive cases. These results suggest that both RV-and RSV-induced wheezing episodes in early childhood are associated with asthma even in adulthood, but perhaps with different asthma phenotypes.…”
Section: Discussionmentioning
confidence: 76%
“…22 The utility of using FeNO to adjust the dose of ICS to reduce exacerbations in asthmatics already receiving treatment has been investigated in several studies with controversial results. 23,24 In this setting, FeNO seems to perform less well that sputum eosinophils.…”
Section: Exhaled Breathmentioning
confidence: 95%